EU peace-building in the north of Kosovo and psychosocial implications for the locals: a bottom up perspective on normative power Europe. Issue 5 (3rd September 2019) - Zupančič, Rok
ABSTRACT: This paper explores what the Brussels Dialogue, a cornerstone of the current EU peacebuilding activities in Kosovo, means for the Serbs living in the north of Kosovo. Many argue that the EU-brokered dialogue is a 'success story' of EU peacebuilding. Yet such positive assessments usually overlook several consequences for the locals and how they perceive this 'success story'. By linking the theory on the EU as a normative power with academic literature on the local aspects of peacebuilding, this paper contends that, despite the apparent success, the EU's peacebuilding approach in Kosovo also brings several negative psychosocial implications for Serbs in the north of Kosovo and have further exacerbated intra-ethnic relations. The contours of intra-ethnic conflict in this territory reached a climax in January 2018 when the prominent Kosovo Serb politician Oliver Ivanovic was assassinated. The increase in a general lack of security in the north of Kosovo, which the EU has also added to by ignoring or not properly addressing the challenges, questions the apparent success of the EU's efforts here while also negatively affecting the overall perception of the EU as a normative power.